Variants of inward disorder pattern and self-awareness features among elementary school children with different dysontogenesis forms - Adeeva, Tatiana; Tikhonova, Inna; Khazova, Svetlana (Social Welfare: Interdisciplinary Approach, 2019)
This study explored variants of inward disorder pattern (IDP) among elementary school children with different dysontogenesis forms. IDP is considered a complex integrative construct that affects I-concept development and is significant for an individual’s successful social adaptation. The sample consisted of 84 participants – elementary school children with visual, hearing, speech impairments, and mental development disorder. Their average age is 9. The interview was conducted individually. We identified a number of specificities in IDP components content depending on a dysontogenesis form. These features are determined by both an impairment itself and component ratios where those between the physical-sensitive, cognitive, and motivational ones are of the greatest significance. Other IDP determinants are such complex self-awareness indices as a level of one’s traits awareness and self-perception in a context of social relationships. The study results suggest three variants of IDP for the moment.